The Dialectic of the Mind and the Text in Islamic Thought (Islamic Sciences Journal, 2023)
ABSTRACT                            There are many who deny that this mind plays a central role in Islamic intellectual life, or they oppose its playing of this role. In our troubled days, many non-Muslims see Islam as a fundamental anti-rational force, citing its alleged failure to adapt or conform to the contemporary world (I don't know what's wrong with that?), and mention the doctrine of martyrdom, and very famous examples of anomalous applications in Islamic jurisprudence, and the modern and general secular skepticism, which is related to religion as an organizing principle of human life, and social and political life in particular.      This is what Imam Al-Ghazali explained by saying: “youshould Know that the intellect will not be guided except by the law, and the law is not clarified except by the intellect. The intellect is like a foundation, and the law is like a building, and a building will not be established unless it is a foundation.  And the beam will not sing unless there is sight.”